Investigation of the genotoxicity of digested titanium dioxide nanomaterials in human intestinal cells - Vieira, Adriana (2022)
The widespread use of titanium dioxide nanomaterials (TiO2 NMs) in food and consumer products such as toothpaste or food contact materials, suggests the relevance of human oral exposure to these nanomaterials (NMs) and raises the possibility of adverse effects in the gastrointestinal tract (GIT). We previously showed that the in vitro digestion of TiO2 NMs may increase their toxicity in intestinal cells. In this work, we analyzed the genotoxicity and the intracellular reactive oxygen species induction by physiologically relevant concentrations of three different TiO2 NMs (NM-102, NM-103 and NM-105) in Caco-2 and HT29-MTX-E12 intestinal cells, while considering the potential influence of the digestion process in the NMs’ physiochemical characteristics. The results evidenced a DNA-damaging effect dependent on the NM, more relevant for the rutile/anatase NM-105, possibly due to its lower hydrodynamic size in the cells medium. In addition, the results of the micronucleus assay suggest effects on chromosomal integrity, an indicator of cancer risk, in the HT29-MTX-E12 cells, for all the tested TiO2 NMs, especially after the in vitro digestion. This work supports the evidence for concerns on the use of TiO2 NMs as a food additive, recently reported by EFSA, and for their use in applications in consumer products that may drive human exposure through ingestion.